1998
DOI: 10.1007/s002470050486
|View full text |Cite
|
Sign up to set email alerts
|

Use of technetium-tagged white blood cells in patients with Crohn's disease and ulcerative colitis: is differential diagnosis possible?

Abstract: These data show that WBC-Tc99m scanning can be useful in distinguishing discontinuous from continuous colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Past experiments have indicated that SPECT-CT imaging may be a useful modality in a DSS model of colitis. In these studies, however, radiolabeled neutrophils or WBCs were administered, precluding the ability to localize and enumerate a specific subpopulation of cells (i.e., CD4 + T cells) (Weldon et al, 1996;Charron et al, 1998;Biancone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Past experiments have indicated that SPECT-CT imaging may be a useful modality in a DSS model of colitis. In these studies, however, radiolabeled neutrophils or WBCs were administered, precluding the ability to localize and enumerate a specific subpopulation of cells (i.e., CD4 + T cells) (Weldon et al, 1996;Charron et al, 1998;Biancone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, small bowel and colon are assessed on the same occasion and screening could accurately distinguish between Crohn's disease and ulcerative colitis. 7,8 The technique has the potential for verifying the presence of abscesses and, possibly, of fistulas. 9,10 The use of leukocyte scintigraphy in guiding therapy has not yet been established.…”
mentioning
confidence: 99%
“…Charron et al,30,31 when reviewing patients studied with technetium‐tagged white cell scans, found this study had some use in distinguishing between Crohn's colitis and UC. Discontinuity of inflammation was evident on scanning but not immediately delineated on endoscopy and biopsy.…”
Section: Discussionmentioning
confidence: 89%